2019
DOI: 10.31124/advance.9853451.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lecturers’ competence and the Quality of University Graduates; The Case of Private and Public Universities in Uganda.

Abstract: This study investigated the effect of lecturer competence on the quality of university graduates in Uganda. Quality of university graduates was measured by satisfaction of students with their current university experience and their labour market expectations. Competency of university lecturers was measured by their content knowledge competency, methods competence, professional competence and techniques that they use to assess students' work. A correlational, cross-sectional survey design was used with quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tahir and Hanapi (2017) agree, stating that the best lecturer is one who possesses expertise in the subject matter and a variety of teaching strategies. Meanwhile, Bagonza et al (2019) identified lecturer characteristics as content knowledge, methods, professional competence, and techniques used to assess students' work. This study, however, conceptualizes lecturer characteristics as attitudes, qualifications, and experience in teaching.…”
Section: Conceptualization Of the Study Variablesmentioning
confidence: 99%
“…Tahir and Hanapi (2017) agree, stating that the best lecturer is one who possesses expertise in the subject matter and a variety of teaching strategies. Meanwhile, Bagonza et al (2019) identified lecturer characteristics as content knowledge, methods, professional competence, and techniques used to assess students' work. This study, however, conceptualizes lecturer characteristics as attitudes, qualifications, and experience in teaching.…”
Section: Conceptualization Of the Study Variablesmentioning
confidence: 99%